El principio Kompetenz-Kompetenz, revisitado a la luz de la Ley de arbitraje comercial internacional argentina - Caivano, Roque J. (2020)
As one of the pillars of international arbitration, the doctrine of kompetenz-kompetenz has a dual function. In a positive sense, it represents the recognition of the existence of an arbitral jurisdiction founded on the parties’ agreement and thus the power of any arbitral tribunal to rule on its own jurisdiction when challenged. In its negative sense, the principle acknowledges the arbitrators’ power to be the first judge to consider and decide on the said jurisdiction when resolving a dispute.In this article, the authors recapitulate the kompe-tenz-kompetenz principle under the light of the recently promulgated Argentina’s International Com-mercial Arbitration Law, emphasizing its various nuances, which sometimes occur unnoticed by national courts. The aim is understanding, through a logic and practical standpoint, the reasonable and balanced distribution between arbitral and judicial roles when the principle is exercised.